Techno-economic Analysis of a Stand-alone Photovoltaic-Diesel Hybrid System for Rural Applications - Harmen, Bin Muda (Universiti Malaysia Sarawak (UNIMAS), 2019)
Photovoltaic hybrid power generation is an alternative solution for supplying electricity to rural areas in Sarawak, Malaysia, where grid connection is almost impossible due to the cost and geographic location. Diesel generator systems are still used by local communities in these remote areas, and the implementation of photovoltaic diesel hybrid systems can reduce dependency on diesel generator units. The work presented in this study explores the possibility of combining a renewable energy resource with diesel generators to meet the load demand of rural communities in Sarawak. The main objective of this study is to determine the optimal configuration and size of the PV-diesel system in terms of net present cost (NPC) and cost of electricity (COE). The optimal configuration of the system is categorized based on the lowest values of NPC and COE, taking into account a minimum value of excess electricity generated. The framework and the generic algorithm of optimizing are modified according to the objectives of this study. The study is based on mathematical modeling and simulation using the Hybrid Optimization Model for Electric Renewables (HOMER) software. Eight different configurations of two energy resources – photovoltaic panels and diesel generators – are studied and compared. The option with the highest optimization values is considered to be the most feasible energy solution for a particular rural area. The outcomes of the study show that the PV-diesel hybrid configuration proves to be more cost-effective compared to an existing generator-based system in that it reduces fuel dependency and has the lowest NPC and COE among all configurations studied. The study also shows the possibility of developing a stand-alone optimized energy configuration for other rural areas in the state. The results are beneficial as a design guide for utility companies or policymakers. Keywords: PV-diesel Hybrid, Net Present Cost, Cost of Electricity, HOMER